Levinas and the Night of Being : A Guide to Totality and Infinity - Moati, Raoul (Book collections on Project MUSE., 2017)
A close reading of Emmanuel Levinas's masterpiece Totality and Infinity which leads to a rehabilitation of the Metaphysical question beyond its deconstructive critique during the XXth Century.